Voltammetric and EPR spectroscopic studies associated with the reduction of pyridine- and benzene-substituted n-alkyl esters and thioic S-esters in aprotic solvents - Webster, R; Bond, A; Compton, R (1996)
The reduction of an extensive series of mono- and disubstituted n-alkyl esters and thioic S-esters has been examined by cyclic voltammetry, differential pulse voltammetry, and hydrodynamic voltammetric techniques in the aprotic solvents acetonitrile and dichloromethane to determine the reversible potentials, the degree of electrochemical and chemical reversibility, and the number of electrons transfered in each process. The compounds can all be reduced by one electron at negative potentials [-1.61 to -2.69 V vs Fc/Fc+] (Fc = ferrocene) with several of the compounds also exhibiting a second reduction step. However, the degree of chemical reversibility of the first reduction process depends critically on the nature of the compound. Correlation of the voltammetric data with substituent effects is also discussed. Many of the compounds produce radical anions upon reduction which are sufficiently stable to enable EPR spectra to be recorded in situ in both channel electrode flow through and stationary solution electrochemical cells. Well-resolved EPR spectra generally could be obtained for all the compounds which displayed chemically reversible voltammetry under conditions of slow scan rate (v < 200 mV s-1) using cyclic voltammetry. The magnitude of the hyperfine splitting constants calculated and the nature of the EPR spectra obtained under different concentration, solvent and temperature regimes is discussed. © 1996 American Chemical Society.